Serum Cystatin C as a Potential Predictor of the Severity of Multiple System Atrophy With Predominant Cerebellar Ataxia: A Case-Control Study in Chinese Population - Ye, Fei; Wang, Tianzhu; Li, Huan; Liang, Jie; Wu, Xiaoxin; Sheng, Wenli (Frontiers in Neuroscience, 2021)
Objective: Multiple system atrophy (MSA) is a serious neurodegenerative disease that is charactered by progressive neurological disability. The aim of this study was to investigate the correlation of serum oxidant factors with the severity of MSA. Methods: A total of 52 MSA patients and 52 age- and gender- matched healthy subjects were retrospectively enrolled in this study. Enzymatic colorimetric methods were used to assay the concentrations of uric acid (UA), serum creatinine (Scr), blood urea nitrogen (BUN), and cystatin C (Cys-C). Disease severity was evaluated by the Unified Multiple System Atrophy Rating Scale (UMSARS). The disease progression rate was defined by the change in UMSARS-IV (global disability score, GDS) over a one-year period. Results: Comparisons between the two groups revealed that there were no significant differences in terms of serum Scr (70.81±13.88 vs. 70.92±14.19 μmol/L, p=0.967). However, the serum levels of the other three biomarkers were significantly higher in the MSA patients (UA: 325.31±84.92 vs. 291.19±64.14 μmol/L, p=0.023; BUN: 5.68±1.67 vs. 4.60±1.24 mmol/L, p<0.001; Cys-C: 0.96±0.15 vs. 0.89±0.14 mg/L, p=0.024). In addition, Pearson correlation analyses revealed that only serum Cys-C was significantly correlated to GDS (r = 0.281, p = 0.044). Subgroup analysis further demonstrated that serum Cys-C was the only factor that was positively associated with the disease severity in patients with MSA and predominant cerebellar ataxia (MSA-C) (r=0.444, p=0.018); there was no significant association in MSA patients with predominant Parkinsonism (MSA-P) (r=0.118, p=0.582). MSA-C patients with severe disability were shown to express higher serum levels of Cys-C than patients with mild disability (1.03±0.13 vs. 0.88±0.12 mg/L, p=0.009). Finally, Kaplan-Meier plots revealed a significant difference in the 5-year probability of survival from severe disability between MSA-C patients with high- and low-concentrations of serum Cys-C (Log-rank test: X2=4.154, p=0.042). ROC curve analysis confirmed that serum Cys-C exhibits good performance as a biomarker (AUC=0.847). Conclusions: Our research indicated that oxidative stress plays a vital role in MSA. Serum Cys-C represents a potential prognostic biomarker to evaluate the severity of disease in patients with MSA-C.